Artificial Intelligence in the post-COVID-19 era - Chymis, Athanasios (Homo Virtualis, 2020)
Artificial Intelligence (AI) dominates the media and has been the focus of public discourse in the last few years. Since last March, however, COVID-19 makes almost everyday headlines because of its huge impact on our highly globalized world. This article has a dual objective. First, it aims to dissolve common misunderstandings and fears regarding AI. Second, by putting AI’s and COVID-19 societal and economic impacts into perspective, it discusses AI applications and research in the post-COVID-19 era. COVID-19 has played a catalytic role in accelerating the use of AI to mitigate the pandemic’s devastating effects. It is up to us to use AI in a responsible and ethical way that includes and benefits the whole humanity.